Honokiol Provides Cardioprotection from Myocardial Ischemia/Reperfusion Injury (MI/RI) by Inhibiting Mitochondrial Apoptosis via the PI3K/AKT Signaling Pathway - Linhua Lv; Qiuhuan Kong; Zhiying Li; Ying Zhang; Bijiao Chen; Lihua Lv; Yubi Zhang (Cardiovascular Therapeutics)
Background. Myocardial injury refers to a major complication that occurs in myocardial ischemia/reperfusion injury (MI/RI). Honokiol is a well-recognized active compound extracted from the traditional Chinese herb known as Magnolia officinalis and is utilized in treating different vascular diseases. This research is aimed at examining whether Honokiol might alleviate myocardial injury in an MI/RI model. Methods. Seventy-eight male C57BL/6 mice were categorized randomly into three cohorts including the Sham operation (Sham) cohort, the MI/RI cohort (Con), and the Honokiol cohort (n=26 for each cohort). The mice in the Honokiol cohort were treated with Honokiol before MI/RI surgery (0.2 mg/kg/day for 14 days, intraperitoneal), while the mice in the Con cohort were given an intraperitoneal injection with an equivalent volume of vehicle (DMSO) daily in 14 days prior to exposure to MI/RI. After the surgery, creatine kinase- (CK-) MB and cardiac troponin T (cTnT) levels, as well as the infarct area, were measured to assess the degree of myocardial damage. Apoptotic levels were detected using terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining. Electron microscopy was utilized to identify mitochondrial damage. Lastly, the expression levels of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), cleaved caspase-9, cytochrome C (Cyt-C), B cell lymphoma/leukemia-2 (Bcl-2), B cell lymphoma/leukemia-2 associated X (Bax), AKT, p-AKT, PI3K, and p-PI3K were analyzed utilizing western blotting. Results. Honokiol can reduce the MI/RI-induced cTnT and CK-MB levels, apoptosis index, and mitochondrial swelling in cardiomyocytes via activating the PI3K/AKT signaling pathway. Conclusion. Honokiol provides cardiac protection from MI/RI by suppressing mitochondrial apoptosis through the PI3K/AKT signaling pathway.